2003
DOI: 10.1261/rna.2130503
|View full text |Cite
|
Sign up to set email alerts
|

A structural, phylogenetic, and functional study of 15.5-kD/Snu13 protein binding on U3 small nucleolar RNA

Abstract: The 15.5-kD protein and its yeast homolog Snu13p bind U4 snRNA, U3 snoRNA, and the C/D box snoRNAs. In U4 snRNA, they associate with a helix-bulge-helix (K-turn) structure. U3 snoRNA contains two conserved pairs of boxes, C/D and B/C, which were both expected to bind the 15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(120 citation statements)
references
References 53 publications
5
114
0
1
Order By: Relevance
“…The ribozyme cleaved an in vitro-transcribed, 32 P-labeled sR29 RNA of 69 nt into fragments of 48 and 21 nt as expected (Fig. 1b, ivt).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The ribozyme cleaved an in vitro-transcribed, 32 P-labeled sR29 RNA of 69 nt into fragments of 48 and 21 nt as expected (Fig. 1b, ivt).…”
Section: Resultssupporting
confidence: 70%
“…The 5Ј and 3Ј termini of linear box C͞D RNAs are normally tethered by base-pairing. This terminal stem contributes to the box C͞D motif (a K turn), which is required for binding by L7Ae and assembly of a functional complex (8,31,32). However, the terminal stem is less, not more, prominent in the sequences of box C͞D RNAs of the hyperthermophilic archaea including P. furiosus (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Snu13p/15.5K has also been implicated in 2 0 O-methylation of preribosomal RNA because of its association with box C/D snoRNPs. [10][11][12] It has been shown that CmSnu13 homologs recognize the kink-turn motif, a purine-rich asymmetrical (5 1 2) internal loop with flanking stems that bend to 658 of each other. 13 Upon binding, the protein acts as a nucleation factor for RNP assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions with both the U4 5 0 stem loop and hPrp31 have been well characterized. 11,[13][14][15][16][17][18] It has also been shown that Prp3p (human 90K) and Prp4p (human 60K) associate and require Snu13p to bind to U4 snRNA prior to their own assembly into the U4 snRNP. 14,20 It is not known what proteins are associated with U4 snRNA prior to assembly of the U4/U6 di-snRNP, but they may include the core Sm and Snu13 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Further examples have been found in mRNA (Mao et al 1999;Winkler et al 2001;Allmang et al 2002;White et al 2004) and in riboswitches (Montange and Batey 2006;Blouin and Lafontaine 2007;Heppell and Lafontaine 2008). They are very commonly found in C/D and H/ACA guide snoRNAs and in U3 snoRNA species (Kuhn et al 2002;Watkins et al 2002;Bortolin et al 2003;Marmier-Gourrier et al 2003;Rozhdestvensky et al 2003;Hamma and Ferré-D'Amaré 2004;Moore et al 2004;Szewczak et al 2005;Youssef et al 2007). There is also a near-canonical k-turn in a stem-loop of the human U4 snRNA (Vidovic et al 2000;Wozniak et al 2005).…”
Section: The Occurrence Of K-turns In Rnamentioning
confidence: 99%